Infrared Localized Surface Plasmon with Curved Electron Trajectory. Issue 19 (3rd July 2022) - Liu, Miao; Zhang, Xinping; Mu, Yunyun; Fu, Yulan; Li, Jiajun; Liu, Yue; Hu, Jingyun
Abstract: The construction of 3D localized surface plasmons (LSPs) in infrared using curved gold nanoshell (AuNS) cylindrical ridges is reported, where the LSPs are found to be established through electronic oscillation in curved trajectories along the perimeter of the cross‐sectional profile of the AuNS cylindrical ridges. Such a design is equivalent to an extension of the electronic trajectory length or plasmonic electron‐oscillation distance by the curvature length and by the enhanced electronic scattering. Strong LSPs are measured for the transverse magnetic polarization perpendicular to the extending direction of the AuNS cylindrical ridges in the spectral range from 1.1 to beyond 2.5 µm, which are not observed for the transverse electric polarization. Such LSPs are strongly dependent on the perimeter length, the curvature angle, and the thickness of AuNSs. The corresponding mechanisms are verified convincingly by both the experimental and theoretical results. These discoveries explore new approaches to designing plasmonic devices in the infrared using nanoscale structures. The 3D scheme with large modulation depth not only facilitates equivalent extending of the dimensions of the metallic nanostructures, but also enlarges interaction volume between plasmons and molecules, implying applications of them in micro‐/nano‐cavity lasers, sensors, or optoelectronic devices based on plasmonic enhancement. Abstract : 3D localized surface plasmons in the infrared are constructed using gold nanoshell cylindrical ridges, which are based on the electronic oscillation in curved trajectories along the wall surface. The resonance spectrum is tuned from shorter than 1100 nm to longer than 2500 nm by extending the electronic trajectory distance by increasing the curvature length or reducing the curvature angle.